Sexual and gender harassment in Swedish workplaces: A prospective cohort study on implications for long-term sickness absence - Katrina Blindow; Fredrik Bondestam; Gun Johansson; Theo Bodin; Hugo Westerlund; Anna Nyberg (Nordic Association of Occupational Safety and Health (NOROSH), 2021)
OBJECTIVES: This prospective cohort study aimed to investigate gender harassment and sexual harassment as risk factors for prospective long-term sickness absence (LTSA, ≥21 days). Furthermore, support from colleagues was investigated as a moderating factor of this association. METHODS: Information on gender harassment, sexual harassment and support by colleagues were derived from the biannual Swedish Work Environment Survey 1999-2013, a representative sample of the Swedish working population (N=64 297). Information on LTSA as well as demographic and workplace variables were added from register data. Relative rates of LTSA the year following the exposure were determined using modified Poisson regression. RESULTS: Monthly to daily exposure to gender harassment was a risk factor for prospective LTSA among women [rate ratio (RR) 1.04, 95% confidence interval (CI) 1.02-1.05] and men (RR 1.07, 95% CI 1.04-1.10). Monthly to daily exposure to sexual harassment was also a risk factor for LTSA among women (RR 1.05, 95% CI 1.01-1.10) and men (RR 1.07, 95% CI 1.02-1.13). Exposure to sexual or gender harassment once in the last 12 months was not associated with LTSA. There was no support for an interaction between either of the exposures and support from colleagues in relation to LTSA. CONCLUSIONS: Sexual harassment and gender harassment appear to contribute to a small excess risk for LTSA among women and men. For both kinds of offensive behaviors, the pervasiveness appears to be important for the outcome. The role of support by colleagues was inconclusive and needs further investigation.